Plant Cell Biology From Astronomy to Zoology - Wayne, Randy (Academic Press, 2009)
Covers various aspects of plant cell biology without emphasizing any one plant, organelle, molecule, or technique. This book explains the physiological underpinnings of biological processes to bring original insight related to plants. It includes examples to bring understanding to plant cell development, growth, chemistry and diseases.